National survey of myeloablative total body irradiation prior to hematopoietic stem cell transplantation in Japan: survey of the Japanese Radiation Oncology Study Group (JROSG). (23rd March 2018) - Ishibashi, Naoya; Soejima, Toshinori; Kawaguchi, Hiroki; Akiba, Takeshi; Hasegawa, Masatoshi; Isobe, Kouichi; Ito, Hitoshi; Imai, Michiko; Ejima, Yasuo; Hata, Masaharu; Sasai, Keisuke; Shimoda, Emiko; et al.
Abstract: A myeloablative regimen that includes total-body irradiation (TBI) before hematopoietic stem cell transplantation results in higher patient survival rates than achieved with regimens without TBI. The TBI protocol, however, varies between institutions. In October 2015, the Japanese Radiation Oncology Study Group initiated a national survey of myeloablative TBI (covering 2010–2014). Among the 186 Japanese institutions performing TBI, 90 (48%) responded. The 82 institutions that had performed myeloablative TBI during this period treated 2698 patients with malignant disease [leukemia (2082 patients, 77.2%), malignant lymphoma (378, 14%)] and 37 with non-malignant disease [severe aplastic anemia (20, 54%), inborn errors of metabolism (5, 14%)]. A linear accelerator was used at all institutions. The institutions were divided into 41 large and 41 small institutions based on the median number of patients. The long source–surface distance technique was the method of choice in the 34 institutions (82.9%) and the moving-couch technique in the 7 (17.1%) in the large institutions. The schedules most routinely used by the participating institutions consisted of 12 Gy/6 fractions/3 days (26 institutions, 63.5%) in the large institutions. The dose rate varied from 5 to 26 cGy/min. The lungs and lenses were routinely shielded in 23 large institutions (56.1%), and only the lungs in 9 large institutions (21.9%). At lung-shielding institutions, the most frequent maximum acceptable total dose for the lungs was 8 Gy (19 institutions, 27.5%). Our results reveal considerable differences in the TBI methods used by Japanese institutions and thus the challenges in designing multicenter randomized trials based on TBI.